A template for an improved rock-based subdivision of the pre-Cryogenian timescale. Issue 1 (January 2022) - Shields*, Graham A.; Strachan, Robin A.; Porter, Susannah M.; Halverson, Galen P.; Macdonald, Francis A.; Plumb, Kenneth A.; Alvarenga, Carlos J. de; Banerjee, Dhiraj M.; Bekker, Andrey; Bleeker, Wouter; Brasier, Alexander; Chakraborty, Partha P.; et al.
No abstract available